Trends and evolution of tourism in the Mediterranean Basin - Almeida-García, Fernando; Balbuena-Vázquez, Antonia; Cortés-Macías, Rafael (My University, 2014)
This study analyzes the tourist developments that have taken the Mediterranean basin in recent years. This paper studies the internal differences, the intervention of political and social factors and key trends. Maintenance of tourism is checked despite the stagnation in tourist arrivals. The Mediterranean basin is the main tourist area of the world, despite strong competition from other tourist areas. The distribution of this tourism is very unbalanced, with most concentrated in the north shore, and especially in the western side (75.4% tourists and 78.9% bed places, 2012). The southern and eastern Mediterranean shore has been affected by conflict which has caused a loss of tourist flows. The Mediterranean basin is a mature tourist region that needs to reinvent itself to remain.
Análisis de las tendencias del turismo en la cuenca del Mediterraneo.
Keywords: Turismo - Mediterraneo (Región); Mediterranean Sea; mar Mediterraneo; Trends; Tendencias; Turismo; Tourism